Adonis Among Virility and the Feminization of the world (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research is based on the assertion that language/writing relies on creativity and creation, and therefore it is viewed from this perspective as a human creativity, whether it be from a woman or a man, the search for a woman's position should be from within the language, because language is enough to guide us to the human vision of the world, and the distinction between the man and the woman depends on visions and contents rather than division and divergence, since they both share one root which is the language, and since the feminist discourse is not limited to the female literature, it rather includes what women or men write about women issues, women’s suffering within the society,  her psychological issues and her constant conflict with the culture that considers her as a subordinate and eliminates her rights.The choice of Adonis relies heavily on him being a poet and an intellectual concerned in one way or another in human issues generally and in women issues specifically, as he considers her the gateway allowing the openness to freedoms and social justice, also, because women issues (from Adoni’s perspective) is one of the most important issues in society, hence, the Arab mind set should address it, as women issues have not been addressed since the renaissance except in less radical, less bold and less profound way than in have been the past.